E3 Ubiquitin Ligase Synoviolin Is Involved in Liver Fibrogenesis - Hasegawa, Daisuke (Public Library of Science, 2010)
BACKGROUND AND AIM: Chronic hepatic damage leads to liver fibrosis, which is characterized by the accumulation of collagen-rich extracellular matrix. However, the mechanism by which E3 ubiquitin ligase is involved in collagen synthesis in liver fibrosis is incompletely understood. This study aimed to explore the involvement of the E3 ubiquitin ligase synoviolin (Syno) in liver fibrosis. METHODS: The expression and localization of synoviolin in the liver were analyzed in CCl(4)-induced hepatic injury models and human cirrhosis tissues. The degree of liver fibrosis and the number of activated hepatic stellate cells (HSCs) was compared between wild type (wt) and Syno(+/−) mice in the chronic hepatic injury model. We compared the ratio of apoptosis in activated HSCs between wt and Syno(+/−) mice. We also analyzed the effect of synoviolin on collagen synthesis in the cell line from HSCs (LX-2) using siRNA-synoviolin and a mutant synoviolin in which E3 ligase activity was abolished. Furthermore, we compared collagen synthesis between wt and Syno(−/−) mice embryonic fibroblasts (MEF) using quantitative RT-PCR, western blotting, and collagen assay; then, we immunohistochemically analyzed the localization of collagen in Syno(−/−) MEF cells. RESULTS: In the hepatic injury model as well as in cirrhosis, synoviolin was upregulated in the activated HSCs, while Syno(+/−) mice developed significantly less liver fibrosis than in wt mice. The number of activated HSCs was decreased in Syno(+/−) mice, and some of these cells showed apoptosis. Furthermore, collagen expression in LX-2 cells was upregulated by synoviolin overexpression, while synoviolin knockdown led to reduced collagen expression. Moreover, in Syno(−/−) MEF cells, the amounts of intracellular and secreted mature collagen were significantly decreased, and procollagen was abnormally accumulated in the endoplasmic reticulum. CONCLUSION: Our findings demonstrate the importance of the E3 ubiquitin ligase synoviolin in liver fibrosis.